2019
DOI: 10.18632/aging.101862
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of recurrent stroke at 5 years after the first-ever stroke in rural China: a population-based stroke surveillance from 1992 to 2017

Abstract: Recent data on the incidence and trends for recurrent strokes in China are scarce. We assessed the temporal trends in recurrent stroke incidence using in rural China. The age-standardized incidences of recurrent stroke, within 5 years of the incident stroke event, were estimated for 3 time periods: 1992–1998, 1999–2005, and 2006–2012. Among the 768 documented incident stroke cases, 26.3% of the patients experienced recurrent stroke within 5 years. The overall age-adjusted recurrent stroke incidence was 43.93 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Contrary to most studies where the rate of oneyear recurrence declined [33,40,41], the recurrence rate in this study increased over the past fifteen years. The rise in stroke recurrence in a rural population as shown by this study is also similar to results from a study in rural China [42]. This disparity in the recurrent stroke trend between urban and rural populations should be further studied.…”
Section: Discussionsupporting
confidence: 87%
“…Contrary to most studies where the rate of oneyear recurrence declined [33,40,41], the recurrence rate in this study increased over the past fifteen years. The rise in stroke recurrence in a rural population as shown by this study is also similar to results from a study in rural China [42]. This disparity in the recurrent stroke trend between urban and rural populations should be further studied.…”
Section: Discussionsupporting
confidence: 87%
“…Recurrent stroke occurs in 11.1% of stroke patients within one year of the initial stroke [1], and is associated with greater disability and mortality [2]. A recent study from China has shown that the incidence of recurrent stroke has increased 3-fold between 1992 and 2012 [3]. Age [4], dyslipidemia [5], smoking [6], diabetes, hypertension, homocysteine levels, atrial fibrillation [1], metabolic syndrome [7] and other risk factors [8][9][10] are associated with recurrent stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 demonstrates 5-year recurrence rates reported in other studies. 15,160,172,173,176,188,194,198,201,207,[258][259][260][261][262][263][264] As for early recurrence, differences in study populations, follow-up, definitions of recurrence and inclusion of hemorrhagic stroke may explain some of the observed differences between studies.…”
Section: Long-term Recurrent Ischemic Stroke or Tiamentioning
confidence: 99%
“…Still, studies on stroke recurrence trends differ on whether recurrence rates are declining in industrialized countries. 168,265,266 Some studies from selected populations indicate a decline in recurrence rates, 175,[267][268][269] other have reported an increase in incidence, 263,270 but a recent metaanalysis estimated the annual recurrent stroke risk to be ≈4.26% without any observable decline over time. 266 A study from the Dijon Stroke Registry reported an increase in recurrent strokes due to improved stroke care and more stroke survivors with longer survival, which is relevant with populations ageing in industrialized countries.…”
Section: Long-term Recurrent Ischemic Stroke or Tiamentioning
confidence: 99%